2015
DOI: 10.1108/cg-04-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

The linkages among intellectual capital, corporate governance and corporate social responsibility

Abstract: Purpose – The purpose of present study is to explore the linkages among Intellectual Capital (IC), Corporate Governance (CG) and Corporate Social Responsibility (CSR) through direct and indirect empirical inquiry. Design/methodology/approach – The main setting is designed for exploring the relationship among IC, CG and CSR. Therefore, these three constructs are examined directly in which their statistical relation is evaluated among them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 34 publications
5
41
1
2
Order By: Relevance
“…Pendelegasian otoritas decision-making oleh principal kepada agent adalah karena harapan principal adalah bahwa agent akan bekerja sesuai dengan kepentingannya (Bonazzi and Islam, 2007). Yang menjadi principal adalah shareholders, sedangkan yang menjadi agent adalah manager/manajemen perusahaan (Altuner et al, 2015;Bonazzi and Islam, 2007). Agency conflict terjadi ketika agent tidak melakukan pekerjaan sesuai dengan kepentingan serta tujuan principal.…”
Section: Teori Agency Dan Teori Stewardshipunclassified
See 1 more Smart Citation
“…Pendelegasian otoritas decision-making oleh principal kepada agent adalah karena harapan principal adalah bahwa agent akan bekerja sesuai dengan kepentingannya (Bonazzi and Islam, 2007). Yang menjadi principal adalah shareholders, sedangkan yang menjadi agent adalah manager/manajemen perusahaan (Altuner et al, 2015;Bonazzi and Islam, 2007). Agency conflict terjadi ketika agent tidak melakukan pekerjaan sesuai dengan kepentingan serta tujuan principal.…”
Section: Teori Agency Dan Teori Stewardshipunclassified
“…Mekanisme corporate governance terdiri dari mekanisme eksternal dan internal (Altuner et al, 2015). Penelitian tersebut mengungkapkan bahwa mekanisme internal adalah mekanisme yang spesifik dan merupakan semua tindakan yang dilakukan oleh perusahaan untuk menerapkan control dan akuntanbilitas.…”
Section: Corporate Governanceunclassified
“…After Tukey had financial stability, the popularity of CSR activities started to go up. In this context, Turkish Social Responsibility Association was founded in 2005 and this association became a member of Europe in 2008 (Altuner et. al., 2015).…”
Section: Page40mentioning
confidence: 99%
“…An overlooked aspect is that most of the research is geographically limited, and the empirical tests are performed on small samples with reference to a specific industry (e.g., References [15,[26][27][28][29][30][31][32][33]). Moreover, some studies adopt univariate tests (e.g., Reference [29]) or adopt cross-sectional data (e.g., Reference [28]) that impede causality examination, whereas other analyses minimize the reverse causality effects (e.g., Reference [15]). In the prior models, the explicative variables are mainly self-constructed through surveys administered to representatives of the sampled companies (e.g., References [15,28]), thus generating somewhat subjective analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The latter can contribute to the development of IC not only through the management Sustainability 2019, 11, 1899 4 of 25 of human resources [15,57] but also through the ethics, transparency. and effectiveness of CG mechanisms, [29,31,32,50]. Indeed, prior literature has found that CG has a significant impact on internal CSR issues, such as employee conditions and the ethical aspects related to managerial and employee behavior [58,59].…”
Section: Introductionmentioning
confidence: 99%